2006
DOI: 10.1016/j.physletb.2006.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behavior of Wilson loops from Schrödinger equation on the gauge group

Abstract: Probability distribution of non-Abelian parallel transporters on the group manifold and the corresponding amplitude are investigated for quantum Yang-Mills fields. It is shown that when the Wilson area law and the Casimir scaling hold for the quantum gauge field, this amplitude can be obtained as the solution of the free Schrödinger equation on the gauge group. Solution of this equation is written in terms of the path integral and the corresponding action term is interpreted geometrically. We also note that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The coefficients in the obtained equation can be expressed in terms of nonperturbative cumulants of the shifted curvature tensor, which are the basic objects in the method of field correlators [6,18,19]. In the limit of a gaussian-dominated QCD vacuum, where only the second-order cumulant survives, this equation reduces to the heat kernel equation, in accordance with the results of [8,9,10]. We suppose that the proposed generalization of the heat kernel equation may be helpful in finding effective action for QCD string which takes into account screening effects.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…The coefficients in the obtained equation can be expressed in terms of nonperturbative cumulants of the shifted curvature tensor, which are the basic objects in the method of field correlators [6,18,19]. In the limit of a gaussian-dominated QCD vacuum, where only the second-order cumulant survives, this equation reduces to the heat kernel equation, in accordance with the results of [8,9,10]. We suppose that the proposed generalization of the heat kernel equation may be helpful in finding effective action for QCD string which takes into account screening effects.…”
Section: Introductionsupporting
confidence: 63%
“…In the approximation of a gaussian-dominated QCD vacuum one assumes that the only non-zero cumulant is the secondorder cumulant [6,18,19]. In this case the equation (29) reduces to the well-known heat kernel equation, in agreement with the results of [8,9,10]:…”
Section: Cumulant Expansionsupporting
confidence: 57%
See 2 more Smart Citations
“…. It can be shown that p [g; C] is the Wilson loop in the regular representation of the gauge group [10,11].…”
Section: Introductionmentioning
confidence: 99%